Age‐dependent loss of seed viability is associated with increased lipid oxidation and hydrolysis. (10th September 2019) - Wiebach, Janine; Nagel, Manuela; Börner, Andreas; Altmann, Thomas; Riewe, David
Abstract: The accumulation of reactive oxygen species has been associated with a loss of seed viability. Therefore, we have investigated the germination ability of a range of seed stocks, including two wheat collections and one barley collection that had been dry‐aged for 5–40 years. Metabolite profiling analysis revealed that the accumulation of glycerol was negatively correlated with the ability to germinate in all seed sets. Furthermore, lipid degradation products such as glycerol phosphates and galactose were accumulated in some seed sets. A quantitative analysis of nonoxidized and oxidized lipids was performed in the wheat seed set that showed the greatest variation in germination. This analysis revealed that the levels of fully acylated and nonoxidized storage lipids like triacylglycerols and structural lipids like phospho‐ and galactolipids were decreasing. Moreover, the abundance of oxidized variants and hydrolysed products such as mono‐/diacylglycerols, lysophospholipids, and fatty acids accumulated as viability decreased. The proportional formation of oxidized and nonoxidized fatty acids provides evidence for an enzymatic hydrolysis of specifically oxidized lipids in dry seeds. The results link reactive oxygen species with lipid oxidation, structural damage, and death in long‐term aged seeds. Abstract : Seeds can stay alive for hundreds of years without light or reduced carbon sources; they are considered to be the longest living mortal life form. This work shows that lipid oxidation and degradation are connected to losses in germination of cereal seeds dry aged for up to 40 years.